Pemikiran Linguistik Ibnu Jinni: Kajian tentang Sifat Bunyi - Rahing, Nurhikmah; Haniah, (Journal of Arabic Education and Linguistics, 2024)
The study of the characteristics of sound is an interesting area to explore due to its significant role in supporting the process of communication and Arabic language skills. This research aims to explain Ibn Jinni's linguistic thoughts on the characteristics of sound. This study used the library research method with a qualitative descriptive approach. Library research method is used to collecting data from existing references and literature that related to Ibn Jinni's linguistic thoughts. The results of this research consist of a study that includes Ibn Jinni's biography, Ibn Jinni's linguistic thoughts on the characteristics of sound, and the comparison of the theories regarding the characteristics of sound between Ibn Jinni and Sibawaih.